A Thermosetting Polyurethane with Excellent Self‐Healing Properties and Stability for Metal Surface Coating. Issue 20 (28th September 2020) - Xu, Heng; Tu, Jing; Xiang, Guifeng; Zhang, Yang; Guo, Xiaode
Abstract: Self‐healing performance of materials can greatly improve the life of materials and reduce their maintenance costs. Therefore, preparation of self‐healing coating materials is expected to be the development trend of coating materials. In this paper, thermosetting polyurethane material (HTPB‐PG‐SS‐TDI) is designed with excellent mechanical performance, thermal stability, acid–base resistance property, and self‐healing capability by introducing SS (4, 4‐dihydroxy diphenyl dithioether) into thermosetting polyurethane chain. Maximum stress of the polyurethane is up to 2.65 MPa, Maximum strain can reach 700%. Self‐healing efficiency of stress can reach above 95%, and it also has efficient function of healing scratch, self‐healing efficiency of scratch is excellent. The polyurethane material is applied to the metal surface coating, which has remarkable self‐healing function to the scratches on the metal surface and significant acid–base resistance. It can be applied to metal surface protection to provide guidance for future research on infrastructure surface coating. Abstract : Based on the principle of disulfide exchange, thermosetting polyurethanes with self‐healing performance are prepared. The polyurethane material has excellent stress heal ability and scratch self‐healing ability. The polyurethane material is applied to the metal surface coating to test the self‐healing performance and acid–base resistance. The results show that the coating has excellent self‐healing performance and acid–base resistance.